Intervisit Variability of Visual Parameters in Leber Congenital Amaurosis Caused by RPE65 Mutations - Roman, Alejandro J. (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. To determine the intervisit variability of kinetic visual fields and visual acuity in patients with Leber congenital amaurosis (LCA) caused by mutations in the RPE65 (Retinal Pigment Epithelium–specific protein 65kDa) gene. METHODS. RPE65-LCA patients (n = 20; ages 11–40 years) were studied on at least two visits separated by fewer than 120 days using Goldmann visual field (GVF) and ETDRS visual acuity (VA) in a retrospective review. GVFs were quantified by computing the spherical coordinates of their vertices and calculating the solid angle subtended, and reported in normalized solid-angle units (nsu) as a percentage of average normal field extent. Repeatability coefficients were calculated using 95% confidence intervals on log(10)-converted variables. RESULTS. Visual field extents in RPE65-LCA spanned a wide range from 4 to 95 nsu. The repeatability coefficient was 0.248 (log(10)nsu), suggesting cutoffs for significant change (in nsu) of +77% for improvement and −44% for worsening. VA in RPE65-LCA ranged from logMAR = 0.14 to 1.96 (20/40 to 20/1250). The repeatability coefficient was 0.170 (logMAR) (±8.5 ETDRS letters). Comparisons with published studies of ungenotyped retinitis pigmentosa showed that the RPE65-LCA patients had higher variability in kinetic field extent. VA variability in RPE65-LCA fell within reported results for retinitis pigmentosa. CONCLUSIONS. Variability data for GVF and VA are provided to permit interpretation of the significance of increases and decreases of these functional outcomes in ongoing and planned clinical trials of therapy for LCA caused by RPE65 mutations.